Tenencia responsable de animales de compañía bajo el enfoque «una salud». Estudio recopilativo - Hugues, Beatriz (2022)
Pet ownership (PO) exerts beneficial effects on the physical and psycho-emotional health of the people with whom they live, even in pandemic contexts. Animals benefit from receiving attention and care and avoiding health risks, based on the «One Health» approach. Considering the contributions and importance of the subject, a compilation study of works carried out by the authors was carried out to determine the perception of the benefits of PO in different population sectors. These were exploratory and descriptive studies, cross-sectional and quantitative conducted at the National Institute of Endocrinology and the main Veterinary Clinic of Havana, in which people responsible for companion animals (PO). These people had chronic diseases (cardiovascular and endocrine-metabolic), sexual and reproductive health conditions (infertility) and sexual identity (homoerotic and transsexual sexual orientation), in different stages of life (middle and elderly), from 2013 to 2020 (during the context of the COVID-19 pandemic). Selfadministered questionnaires prepared by the research team were used. The results were processed using descriptive statistics and ethical aspects were considered. Most of the participants expressed satisfaction with PO, perceived its benefits on their physical and emotional health, motivated them to take better care of themselves and engage in physical activities, and during the COVID-19 pandemic. Besides, PO decreased the negative effects of social distancing. Dogs and cats were the preferred animals for emotional reasons.